The Obesity Paradox Revisited: Is Obesity Still a Protective Factor for Patients With High Comorbidity Burden or High-Complexity Procedures? - Hyo Jin Son, BSc; Denise W. Gee, MD; David Gomez, MD, PhD; James J. Jung, MD, PhD (Annals of Surgery Open)
Objective:. To investigate the relationship between obesity and postoperative mortality in the context of high procedural complexity and comorbidity burden. Background:. The “obesity paradox” suggests better postoperative outcomes in patients with higher body mass index (BMI), despite obesity’s associated health risks. Research remains scarce on the influence of procedural complexity and comorbidities on the obesity–postoperative mortality relationship. Methods:. We performed an observational study of adult patients undergoing major surgery using the 2016 to 2019 National Surgical Quality Improvement Program database. The outcome was 30-day mortality. We first estimated the risk-adjusted effects of BMI on mortality across the full cohort via multivariable regression and restricted cubic spline models. Then, we investigated the subgroups stratified by procedural complexity and comorbidity burden using a modified Charlson Comorbidity Index (mCCI) and mortality probability. Results:. Among 3,085,582 patients, 47% had obesity. There was a reverse J-shaped relationship between BMI and mortality in the full cohort, consistent with the obesity paradox. However, no difference in odds of mortality was observed in patients with obesity who underwent high-complexity procedures compared with normal BMI counterparts (BMI 30–34.9: odds ratio, 0.93 [95% confidence interval: 0.86–1.01]; BMI 35–39.9: 0.92 [0.83–1.03]; BMI ≥ 40: 0.94 [0.83–1.07]), and in patients with obesity with high comorbidity burden (mCCI ≥ 8 [BMI 30–34.9: 0.95 (0.77–1.16); BMI 35–39.9: 0.78, (0.60–1.02); BMI ≥ 40: 0.84 (0.63–1.12)] and top 3% mortality probability [BMI 30–34.9: 0.96 (0.90–1.02); BMI ≥ 40: 0.94 (0.86–1.01)]). Conclusion:. Our findings suggest the existence of an obesity paradox in most adult surgical patients, yet the trend dissipates with high procedural complexity and comorbidity burden.